HYPERPARATHYROIDISM IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Ali, Humaira; Baig, Jawed Altaf; Alam, Junaid Mahmood (Pakistan Journal of Physiology, 2017)
Background: Chronic kidney disease (CKD) has a high mortality rate and is an inevitable consequence of many kidney diseases. This study assessed incidence of hyperparathyroidism in patients with CKD. Methods: This was a retrospective observational study. A total of 300 samples were screened, out of which 165 were selected which included 96 males and 67 females. The blood levels of iPTH, urea, creatinine, calcium, magnesium, phosphorus and albumin were analyzed using electro-chemiluminescence technology (iECL) on Cobas e411 for iPTH and spectrophotometric technology on Cobas c501 for the rest of the parameters. Results: All the patients had abnormal renal function, out of which 29.7% had normal iPTH levels and 70.3% had elevated iPTH levels. Normal iPTH was seen in 19.4% males and 10.3% females, whereas in the elevated iPTH was seen in 40% males and 30.3% females. The t-test between normal and abnormal iPTH showed a significant correlation (p<0.05) between iPTH, urea, creatinine and albumin levels, whereas no significant correlation was seen with calcium, magnesium and phosphorus levels. Conclusion: There was a positive correlation between iPTH levels and levels of urea, creatinine, and albumin exhibiting increased iPTH levels in CKD patients suggesting underlying secondary hyperparathyroidism. Pak J Physiol 2017;13(2):49–51